Perceived advantages in the use of e-exam – comparative TAM-model study among students and teachers - H. Aramo-Immonen; K. Liikamaa; A.M. Felicetti (Spain, 2022)
Exploratory survey about the transformation from traditional examinations to e-exams. This study was conducted among the higher education students and teachers in technical university and business school in Finland. We wanted to find out the perceived usefulness and ease-of-use of e-exam system among students and teachers. Furthermore, we wanted to compare the attitude and acceptance rate of students and teachers towards the new system. The research was conducted in the phase where there was still possibility to choose between traditional examination in lecture hall with pen and paper and novel electronic examination.
EDULEARN17 Proceedings